STEWARD EMPLOYEE PERFORMANCE FOOD AND BEVERAGE DEPARTEMENT GRAND JATRA HOTEL PEKANBARU - Nitasari, Wahyu; Sidiq, Siti Sofro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Grand Jatra Hotel Pekanbaru is a business owned by the PAM Group. PAM Group stands for Pintu Air Mas which is a company that has various business fields. PAM Group was founded by Addy Sumasto Tjia. On 27 February 2005 the PAM Group established a ***** hotel located in Pekanbaru under the name Grand Jatra Hotel Pekanbaru. Hotel Grand Jatra Pekanbaru is located in a very strategic location, namely at Jalan Tengku Zainal Abidin No 1 Kompleks Pekanbaru Mall, guests can not only expect easy access to the hotel, but also can easily reach all locations in Pekanbaru. The importance of a steward's performance in completing his / her job greatly affects the quality of employee work, especially so that the work area is clean so that it can produce hygienic and healthy products, and it is easy to find equipment to use at work. This research was conducted to determine how the quality of steward employee performance in completing their work. This study uses qualitative methods, while the data collection techniques in this study use observation, in-depth interviews, and documentation. The key informants in this study were 3 steward employees. Based on the results of the research conducted, overall the results of the interviews stated that the performance of steward employees at the Grand Jatra Hotel Pekanbaru still needed to be improved and their discipline was improved.Keywords: Performance, Steward, Food and Beverage Department